2011
DOI: 10.1111/j.1399-0012.2011.01438.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac function and aminoterminal pro‐brain natriuretic peptide levels in liver‐transplanted cirrhotic patients

Abstract: In cirrhotic patients, diastolic function and cardiac structure deteriorate after LT. Compared to controls, NT-proBNP levels tend to be higher before and after transplantation. The mechanisms and consequences of these results require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
11
1
Order By: Relevance
“…Henriksen et al (2003) reported that BNP levels were related to markers of cardiac dysfunction, such as QT interval, heart rate, and plasma volume. In contrast to previ-ous studies (Padillo et al, 2010;Bernal et al, 2012), there was no relationship between BNP concentration and QTc interval identified in our research. It has been reported that a level of BNP over 500 pg/mL is diagnostic for the congestive heart failure presented and diagnosed by a lower ejection fraction on echocardiographic examination (Buğdaycı and Sökmen, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…Henriksen et al (2003) reported that BNP levels were related to markers of cardiac dysfunction, such as QT interval, heart rate, and plasma volume. In contrast to previ-ous studies (Padillo et al, 2010;Bernal et al, 2012), there was no relationship between BNP concentration and QTc interval identified in our research. It has been reported that a level of BNP over 500 pg/mL is diagnostic for the congestive heart failure presented and diagnosed by a lower ejection fraction on echocardiographic examination (Buğdaycı and Sökmen, 2012).…”
Section: Discussioncontrasting
confidence: 99%
“…According to literature, in our study we found a significant increase in cardiac mass, atrial volume and diastolic dysfunction in HCV‐related cirrhotic patients . The increase in left ventricular mass is due to volume overload secondary to expansion of blood volume and activation of neuro‐hormonal systems commonly observed in these patients .…”
Section: Discussionsupporting
confidence: 69%
“…[18,20] On the other hand, Li et al also showed that the prolonged QTc interval duration became normal in 17 of 20 patients undergoing liver transplantation, [19] indicating the impact of liver cirrhosis on heart function. [21,22] Additionally, QTc interval was found weakly associated with MELD score. The proportion of QTc prolongation had an upward tendency with the increase of Child-Pugh grade.…”
Section: Discussionmentioning
confidence: 99%